2012
DOI: 10.1136/sextrans-2011-050283
|View full text |Cite
|
Sign up to set email alerts
|

Why do condoms break? A study of female sex workers in Bangalore, south India

Abstract: Condom use among Bangalore FSWs is now very high. However, condom breakage is still a not uncommon event and puts women and their clients at unnecessary risk of infection. It may be difficult to eliminate the problem completely, but every effort should be made to discuss with sex workers the findings of this survey that point to possible personal markers of risk seen in the univariate analysis and to highlight the importance of avoiding rough sex and of ensuring the condom fits the client.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Within criminalised environments, physical and sexual violence in the workplace, whether by clients, police, managers, pimps, or predators posing as clients, are among the most ubiquitous and influential determinants of HIV acquisition and transmission risk among FSWs, linked to inconsistent condom use, client condom refusal, condom use failure and breakage,22, 24, 26, 28, 33, 43, 46, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57 and HIV infection. 5, 33, 58, 59, 60, 61, 62 In addition to police abuse as a human rights violation, law enforcement strategies and local policing of sex work, including arrests and incarceration, 26, 38, 61, 63, 64, 65 raids, 64 displacement, 24 and confiscation of condoms or syringes, 64, 66 are key barriers to HIV prevention efforts among FSWs worldwide, which reduces or eliminates the ability to negotiate male condom use 24, 51, 61, 63, 64, 66 and increases HIV prevalence and incidence.…”
Section: Structural Determinants Of Hivmentioning
confidence: 99%
“…Within criminalised environments, physical and sexual violence in the workplace, whether by clients, police, managers, pimps, or predators posing as clients, are among the most ubiquitous and influential determinants of HIV acquisition and transmission risk among FSWs, linked to inconsistent condom use, client condom refusal, condom use failure and breakage,22, 24, 26, 28, 33, 43, 46, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57 and HIV infection. 5, 33, 58, 59, 60, 61, 62 In addition to police abuse as a human rights violation, law enforcement strategies and local policing of sex work, including arrests and incarceration, 26, 38, 61, 63, 64, 65 raids, 64 displacement, 24 and confiscation of condoms or syringes, 64, 66 are key barriers to HIV prevention efforts among FSWs worldwide, which reduces or eliminates the ability to negotiate male condom use 24, 51, 61, 63, 64, 66 and increases HIV prevalence and incidence.…”
Section: Structural Determinants Of Hivmentioning
confidence: 99%
“…Recent studies of interpersonal factors associated with HIV infection include number [26], frequency or type of commercial/partnership dyads (e.g., clients, intimate, or causal nonpaying partners) [2628], types of sex acts or exchanges [26], and negotiation of male or female condom use (including, client condom refusal, or condom breakage). Studies of interpersonal HIV factors have also begun to identify how types and characteristics of sex worker–client and intimate or other nonpaying partner relationships shape sexual patterning and HIV transmission dynamics.…”
Section: Epidemiology Of Interpersonal Hiv Factorsmentioning
confidence: 99%
“…Studies of social features of the work environment have primarily focused on the relationship of physical and/or sexual violence (by clients, intimate partners, police, pimps, strangers, or other third parties) to HIV infection [22,40,55,68] and risk among FSWs, either directly through increased risk of transmission (e.g., tearing, forced sex, condom breakage) or indirectly through reduced odds of condom use [26,28,40,41,45,49,79,8587]. Although recognition of intimate partner violence as a global human rights and public health priority has led to standardized measurements and assessments, measurements, and methods related to violence perpetrated against sex workers in the workplace have received limited attention [88].…”
Section: Epidemiology Of Structural Determinantsmentioning
confidence: 99%
“…Sambasivan et al's (2011) innovative phone broadcasting system on microfinance, healthcare announcements, and reminders for urban sex workers in India found that mobile phones were an important and viable tool for non-governmental organizations (NGOs) to communicate with their constituencies. In a mobile phone-based survey of FSWs' sexual behaviours in India, researchers reported a successful and enthusiastic uptake of the methodology resulting in high-response rates especially given the low literacy levels and emphasized the viability of this method for data collection on sensitive topics (Bradley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%